Urban thinkers campus (The United Nations University) - Voon, Boo Ho (Universiti Teknologi MARA, Sarawak, 2016)
The Urban Thinkers Campus on Health and Wellbeing in The City We Need was held from 24 to 27 January 2016 at Pustaka Negeri Sarawak in Kuching. It was a successful international event with more than 170 participants from 28 nations. UiTM Sarawak was invited to assist in co-organising the event to promote the sustainable development of healthy cities for better quality of life worldwide. Our Rector, Professor Dato Dr. Jamil Haji Hamali, kindly and promptly agreed to the request from the Director, Mr. Anthodny Capon of The United Nations University — The International Institute for Global Health (UNU-IIGH). Thereafter, the Research Fellow of UNU-IIGH (Ms Uta Dietrich) worked closely with the Service Research Group (ServGroup, UiTM Sarawak) and MASA (Intitute of Management Sarawak) to plan and implement the event.